Essays on the information-usefulness of changes in fair values to investors and debtholders, and its effect on audit fees : evidence from Australian real estate industry : a thesis presented in partial fulfilment of the requirements for the Degree of Doctor of Philosophy in Accountancy at Massey University, Auckland, New Zealand - Sangchan, Pinprapa (Massey University, 2019)
This research investigates the decision usefulness of changes in fair value (hereafter, CFV) of investment property reported under IAS 40 and IFRS 13 to capital providers (i.e., equity investors and debtholders), using Australian Real Estate Industry data.¹ The motivation for this study stems from the ongoing debate on the beneficial effects of fair value reporting and their associated reliability trade-off (Barth, 2018; Power, 2010). This research further investigates the effect of change in fair value (CFV) of investment property on the monitoring cost proxied by audit fees in order to picture the pros and cons of the subjectivity involved in the fair value accounting-model. The alert issued by the International Auditing and Assurance Standards Board (IAASB) to discuss challenges in auditing fair value accounting estimates, and inconsistent evidence on the effect of the fair value application on audit fees motivate me to study the association between fair value application and monitoring cost. The decision usefulness of CFV study and the effect of fair value reporting on audit fees are organised into three different research essays: (i) value relevance of CFV and measurement-related fair value disclosure to equity investors; (ii) the decision usefulness of CFV and cost of debt; and (iii) fair value exposure, CFV, and audit fees. Essay One investigates the value-relevance of changes in fair values of investment property recorded under IAS 40 and IFRS 13. Using hand-collected data from the Australian Real Estate Industry, I find that changes in fair values of investment property are value-relevant for equity investors. I further find that the use of unobservable inputs in an active market (Level 3 inputs) does not diminish the fair value information content. I document that properties valued exclusively by directors have a significantly reduced value-relevance for their value changes, whereas property valuations made collectively by both directors and independent valuers have superior value relevance, possibly owing to the combination of inside knowledge and externally imposed monitoring. Collectively, the findings suggest that, in the real estate industry, where unobservable inputs are commonly used to determine fair values of properties, the fair values determined subjectively are perceived to be sufficiently informative and relevant. My findings have important implications for accounting standard-setters in considering whether an external valuation should be required and whether the extensive measurement-related fair value disclosure requirements are useful. Essay Two examines the decision usefulness of CFV of investment property reported under IAS 40 and IFRS 13 to debtholders. Using hand-collected data, the findings suggest that CFV of investment property lowers the cost of debt, implying that the fair value information is decision-useful to debtholders. The effect is more pronounced when the CFV is recognised as a gain. The results further suggest that unobservable inputs used for fair value measurement in an active market (Level 3 inputs) do not necessarily damage fair value information content. I also document that using the stand-alone director valuation in fair value estimates for investment properties diminish the information content of such fair value changes, even though director valuation is insightful in terms of asset-specific knowledge. In addition, I report that an extensive fair value measurement-related disclosure does not enhance the information content of fair value changes. Collectively, the findings suggest that in the real estate industry, where unobservable inputs are predominantly used to measure fair values of properties, debtholders view fair values sufficiently faithful and decision useful. Essay Three investigates the relationship between audit fees and both fair value exposure (the proportion of investment property to total assets), and changes in fair value, of investment properties. This study is motivated by the limited and inconclusive evidence on the effect on audit fees of full fair value reporting for illiquid assets. Using hand-collected data from the Australian real estate industry, I find a negative (positive) association between audit fees and fair value exposure (changes in fair values of investment properties). Findings also indicate that the use of unobservable inputs in fair value estimates for investment properties does not significantly increase audit risk and audit fees. Further, I find that audit fees are higher for firms having fair values of investment properties estimated by external and mixed valuers, compared to firms having fair values estimated by directors alone. This study enriches the audit fee literature by documenting auditors’ pricing decisions in an area that involves significant estimation and valuation risks. ¹ Decision-usefulness versus information usefulness are used interchangeably in this thesis.
Keywords: Fair value; Australia; Accounting; Real estate investment; Auditing; Costs; fair value measurement; changes in fair values; value relevance; decision usefulness; cost of debt; audit fees; real estate industry